2017
DOI: 10.1115/1.4036248
|View full text |Cite
|
Sign up to set email alerts
|

Evolutions of Pressure Fluctuations and Runner Loads During Runaway Processes of a Pump-Turbine

Abstract: The pressure fluctuations and runner loads on a pump-turbine runner during runaway process are very violent and the corresponding flow evolution is complicated. To study these phenomena and their correlations in depth, the runaway processes of a model pump-turbine at four guide vane openings (GVOs) were simulated by three-dimensional computational fluid dynamics (3D-CFD). The results show that the flow structures around runner inlet have regular development and transition patterns—the reverse flow occurs when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Figure 4a shows the results of grids independence tests, when the number of grids is more than 5.0 million, the differences of macro-parameters, such as the discharge and moment, are smaller than 0.5% between the different levels, and the parameters match the rated parameters of the turbine. The tests shows that the simulation while using such mesh can give reasonable results [20]. Besides, the grids independence tests for the transient process were conducted, the three tests showed a similar trend, and the differences between 5.11 million and 6.20 million were very small ( Figure 4b).…”
Section: Geometry and Meshmentioning
confidence: 76%
See 1 more Smart Citation
“…Figure 4a shows the results of grids independence tests, when the number of grids is more than 5.0 million, the differences of macro-parameters, such as the discharge and moment, are smaller than 0.5% between the different levels, and the parameters match the rated parameters of the turbine. The tests shows that the simulation while using such mesh can give reasonable results [20]. Besides, the grids independence tests for the transient process were conducted, the three tests showed a similar trend, and the differences between 5.11 million and 6.20 million were very small ( Figure 4b).…”
Section: Geometry and Meshmentioning
confidence: 76%
“…For the prototype turbine in this study, it is impossible to make y + = 1 because the Reynolds number is very high; in order to ensure the accuracy of the k-ω SST, two equation turbulence model, the y + value was more than 30 in the whole domain, so that the wall function approach can be used in the simulation. The timestep was set to 0.001 s, which corresponds to 1.5 degrees of runner rotation at the rated speed [20][21][22]. The SIMPLEC scheme was used in pressure-velocity coupling.…”
Section: Numerical Settingsmentioning
confidence: 99%
“…Tetrahedral meshes were used in the spiral-case; wedge meshes were employed in the guide-vanes; structured hexahedral meshes were applied in the runner and draft-tube ( Figure 2b). Mesh independence checks for different GVO conditions have been conducted in our previous works [23,24]. When the number of gird elements is more than 4.0 million, the relative error of macro parameters among each mesh generation was less than 0.3%, indicating that the numerical simulation results are reasonable.…”
Section: Pump-turbine Modelmentioning
confidence: 98%
“…In addition, the shape of the runner blade leading edge has a significant influence on their evolution, which cannot be explained by the aforementioned one-dimensional models. Many studies have shown that various flow patterns, such as flow separations, backflows, rotating stall, and vortex ropes, will be formed and developed in the flow passages when the pump-turbine operates at the runaway process [21][22][23][24][25]. Nevertheless, finding the key flow patterns responsible for the runaway oscillation stability and revealing their influence mechanism on the stability are the prerequisites for solving the problem at its source.…”
Section: Introductionmentioning
confidence: 99%
“…In the two equations, n referred to the runner speed in revolutions per second, and Z gv and Z b were the number of guide vanes and rotating blades, respectively. Xia et al [21] investigated the pressure fluctuations and runner loads on a Francis pump-turbine runner during the runaway process, and found that the variation of discharge was the main reason for the intense fluctuation in hydraulic thrust during this process. However, limited studies are associated with the pulsating property of hydraulic axial thrust under the impact of multiple hydraulic excitation forces.…”
Section: Introductionmentioning
confidence: 99%